Structural insight into the macrocyclic inhibitor TPX-0022 of c-Met and c-Src - Lingzhi Qu; Hang Lin; Shuyan Dai; Ming Guo; Xiaojuan Chen; Longying Jiang; Huajun Zhang; Maoyu Li; Xunjun Liang; Zhuchu Chen; Hudie Wei; Yongheng Chen (Computational and Structural Biotechnology Journal, 2023)
c-Met has been an attractive target of prognostic and therapeutic studies in various cancers. TPX-0022 is a macrocyclic inhibitor of c-Met, c-Src and CSF1R kinases and is currently in phase I/II clinical trials in patients with advanced solid tumors harboring MET gene alterations. In this study, we determined the co-crystal structures of the c-Met/TPX-0022 and c-Src/TPX-0022 complexes to help elucidate the binding mechanism. TPX-0022 binds to the ATP pocket of c-Met and c-Src in a local minimum energy conformation and is stabilized by hydrophobic and hydrogen bond interactions. In addition, TPX-0022 exhibited potent activity against the resistance-relevant c-Met L1195F mutant and moderate activity against the c-Met G1163R, F1200I and Y1230H mutants but weak activity against the c-Met D1228N and Y1230C mutants. Overall, our study reveals the structural mechanism underlying the potency and selectivity of TPX-0022 and the ability to overcome acquire resistance mutations and provides insight into the development of selective c-Met macrocyclic inhibitors.